The Oxford handbook of India's national security - Ganguly, Sumit 1954-; Blarel, Nicolas 1983-; Pardesi, Manjeet S. (The Oxford handbooks, 2018)
India faces an array of national security challenges. Externally, they range from geopolitical tensions and territorial disputes with China and Pakistan, nuclear deterrence, and state-sponsored/backed cross-border terrorism to the internal security issues related to secessionism, counter-insurgency, Naxalism, and ethnic conflict. In recent decades, the national security agenda has been expanded to include issues related to economics, environment, development, and transnational criminal activities. More than two decades of rapid economic growth has also added energy security to the national security matrix. Concomitant with its economic rise, India's national security agenda also includes a more proactive vision for the wider Asian region, including the Indian Ocean, with implications for power projection, and for India's contributions to global peacekeeping missions through the United Nations. This handbook is the first comprehensive analysis of all these national security challenges, traditional and non-traditional, facing India. With contributions from some of the leading and rising scholars from across the world, the essays cover a wide range of topics and issues including the colonial legacy, realist/liberal/constructivist approaches to national security, India's wars, strategic culture, conventional military challenges including issues of military modernization and defence-industrial challenges, nuclear security, the role of space, cybersecurity, terrorism, insurgencies, the role of the intelligence agencies, civil-military relations, and the relationship between national security and state-making in India